A flexicurity labor market during recession - Torben M. Andersen (IZA World of Labor, 2015)
Before the great recession of 2008–2009, the “flexicurity” model (with flexibility for firms to adjust their labor force along with income security for workers through the social safety net) attracted attention for its ability to deliver low unemployment. But how did it fare during the recession, especially in Denmark, which has been highlighted as having a well-functioning flexicurity model? Flexible hiring and firing rules are expected to lead to large adjustments in employment in a recession. Did the high rate of job turnover continue or did long-term unemployment rise? And did the social safety net become overburdened?
Keywords: E24; J4; J6; 330; flexicurity; employment adjustment; job flows; structural unemployment